Servant Leadership in Japan: A Validation Study of the Japanese Version of the Servant Leadership Survey (SLS-J) - Kobayashi, Yuka; Watanabe, Kazuhiro; Otsuka, Yasumasa; Eguchi, Hisashi; Kawakami, Norito; Imamura, Kotaro; van Dierendonck, Dirk (Frontiers in Psychology, 2020)
Purpose : The purpose of this study is to develop and validate a Japanese version of the Servant Leadership Scale and to clarify the relationship between servant leadership (SL) and well-being among Japanese workers. Methods : After the Japanese version of the SLS (SLS-J) and of its short form (SLS-J-short) were developed in conformity with the guidelines (Wild et al., 2005), a web-based survey was administered to 516 Japanese employees (20 or older and have a supervisor). Confirmatory factor analysis (CFA) was conducted to evaluate a construct validation of the SLS-J and the SLS-J-short. Convergent validity was estimated with theoretically related constructs (e.g., transformational leadership, supervisory support, and interpersonal justice) and potential consequences of SL (e.g., affective commitment, work engagement, job satisfaction, organizational citizenship behavior (OCB), psychological distress, and work performance). Intraclass correlation coefficient (ICC) using the test-retest method was conducted with 104 of the initial respondents to assess internal consistency reliability. Additionally, the effects of SL on employees’ work engagement and the mediating role of employees’ affective commitment were estimated. Results : CFA confirmed that an eight-factor model (SLS-J) and a five-factor model (SLS-J-short) had the most satisfactory fits for the two scales with Japanese workers. Tests of convergent validity and reliability showed sufficiency for each of the dimensions of SLS-J and SLS-J-short. Additionally, it was revealed that SL has an impact on employees’ work engagement through a mediation of affective commitment at a cross-sectional level, and the indirect association between SL and work engagement via affective commitment remained afterwards. Conclusion : SLS-J and SLS-J-short were confirmed to have good reliability and validity for Japanese workers. Also, this study found that SL has an important role in enhancing workers’ engagement.